Frictional behavior of bearing material under gas lubricated conditions - Abdollah, Mohd Fadzli bin; Mazlan, Mohd Afiq Azfar; Amiruddin, Hilmi; tamaldin, noreffendy (2014)
In this study, a Taguchi method is employed to determine statistically the optimal design parameters, and investigate the effect of gas lubrication on friction behavior of bearing material, which is carbon chromium steel. By selecting L9 Taguchi's orthogonal arrays, nine sliding tests were carried out in air, O2- and N2-gas lubrication in accordance with the ASTM standard G99-95a. The test was performed over a broad range of applied loads (W), sliding velocities (v) and sliding distances (L) using a ball-on-disc tribometer. At higher applied load, sliding speed and sliding distance, it was found that gas blown to the sliding surfaces in air effectively reduced the coefficient of friction as compared with the air lubrication. In addition, based upon the mean of signal-to-noise (SN) ratio analysis, the sliding speed is the most influencing factor for minimizing coefficient of friction. In this study, the optimal design parameters for a lower coefficient of friction () are: lubricant = N2, W = 10N, v = 1000rpm, L = 1km. By using the optimal design parameters, a confirmation test successfully verify the N2-gas lubrication reduced coefficient of friction by 24%. This is in accordance with a significant reduction of wear scar diameter and smoother worn surface on a ball.